Bank Business Sustainability: Bibliometric Analysis - Yenny Verawati; Made Kembar Sri Budhi; Ni Putu Wiwin Setyari; I Made Endra Kartika Yudha (Journal of Corporate Finance Management and Banking System, 2024)
Economic development that only focuses on growth often has negative impacts, encouraging the emergence of the concept of sustainable development that balances economic, environmental, and social aspects. This concept, supported by the United Nations and various parties, is the basis for sustainable development goals until 2030, covering human, social economic, and environmental development. Sustainability, introduced in 1987, integrates environmental, social, and economic aspects or the triple bottom line in business standards and practices. The development of sustainable banking is still in its infancy, with some banks starting to adopt environmental and social policies. This research examines risk policies to support sustainable development in commercial banking through an analysis of 50 articles. The results show that economic and social efficiency, stability, and environmental contribution are important in assessing bank sustainability. Internal factors such as risk management and financial health, as well as external factors such as regulations and macroeconomic conditions are very influential.